The role of academics in increasing organizational productivity - Purwanto, Agus (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
Academics have an important role in increasing productivity and work conductivity in the industrial environment, both nationally and globally. A synergistic relationship between academics and the industrial world can create innovations and solutions that support economic growth and work efficiency. The design of this study is a Literature Review; Literature review studies are used to collect data or synthesise sources related to research topics from various sources, including journals, books, documentation, the internet and libraries. The literature study method is a series of activities related to the method of collecting library data, reading and recording, and managing writing materials—the method of searching for articles in research journal databases and searching via the internet. The database search used is Google Scholar from 2019 to 2024. For article searches, the keywords used are also included in the data collection, namely "the role of academics to improve performance". Increasing work productivity is crucial in creating harmonious industrial relations at the global and company levels. With higher productivity, companies can improve employee welfare through better wages, more comfortable working conditions, and reducing industrial conflict. This impacts the stability of the relationship between workers and management, ultimately creating a more conducive work environment. In addition, optimal productivity also contributes to increasing the company's competitiveness in the global market. Companies can produce high-quality products at more competitive prices with operational efficiency, technological innovation, and strengthening international business networks. This allows for broader market expansion and strengthens the industry's position in the global arena.